Relapsed childhood acute lymphoblastic leukemia: Current situation in China; a multicenter observational study - Qun Hu; Wenting Hu; Xiaojuan Chen; Shaoyan Hu; Yiping Zhu; Wei Tang; Xiaofan Zhu; Junjie Fan; Yali Su; Tianyi Wang; Jingyan Tang (Elsevier, 2018)
Background: Relapse is the major reason for death in pediatric acute lymphoblastic leukemia (ALL) patients. It may be worse because of refusing re-treatment in developing countries. So, we investigated the influencing factors for re-treatment decision made by parents and survival data of patients with relapsed pediatric ALL in China. Methods: Clinical characteristics, choice of re-treatment, survival status at the last follow-up time were collected, survival data and prognostic factors were analyzed. Results: Among 390 relapsed cases which were collected from five centers in China, 230 (59.0%) were re-treated. Fifty-eight were alive, 249 had died, and 83 were lost to follow up (median follow up 73.0 months). Receiving retreatment was not associated with gender, initial immunophenotype, or era of relapse, but was associated with age, initial risk group, and recurrence time and site. The 5-year OS rate of patients who received re-treatment or not was 35.5% and 4.5%, respectively. In re-treatment group, the survival analysis showed that initial risk group, site of relapse, time from diagnosis to relapse, and whether the patient achieved CR2 were closely related to 5-year OS, while WBC count (50 × 109/L), and immunophenotype at diagnosis were not. Fortyeight cases received transplantation and 20 (41.7%) survived, while only 36 (19.8%) of 182 patients who did survived. Conclusions: The estimated 5-year OS rate was only 24.4% ± 2.5% for all 390 relapsed cases in China. Of them, 59% patients, 230 cases, were re-treated with 5-year OS 35.5%. Patients who were indicated and performed for HSCT had a 5-year OS of 52.2%. Keywords: Children, Leukemia, Lymphoblastic, Acute, Relapse